2022
DOI: 10.3389/fgene.2022.879974
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers for Predicting Ovarian Reserve of Primordial Follicle via Transcriptomic Analysis

Abstract: Ovarian reserve (OR) is mainly determined by the number of primordial follicles in the ovary and continuously depleted until ovarian senescence. With the development of assisted reproductive technology such as ovarian tissue cryopreservation and autotransplantation, growing demand has arisen for objective assessment of OR at the histological level. However, no specific biomarkers of OR can be used effectively in clinic nowadays. Herein, bulk RNA-seq datasets of the murine ovary with the biological ovarian age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Recently, single-cell bisulfite and proteomic strategies have been reported and have potential to be highly valuable for the study of early embryonic development in the future [91][92][93][94][95]. The restriction to and abundance of PADI6 in the oocyte and early embryo do hold some clinical advantages; for example, recent studies have highlighted the potential to use PADI6 as a novel marker for oocyte and embryo quality as well as ovarian reserve in women receiving assisted reproductive technologies [96,97].…”
Section: What Are the Functions Of Padi6?mentioning
confidence: 99%
“…Recently, single-cell bisulfite and proteomic strategies have been reported and have potential to be highly valuable for the study of early embryonic development in the future [91][92][93][94][95]. The restriction to and abundance of PADI6 in the oocyte and early embryo do hold some clinical advantages; for example, recent studies have highlighted the potential to use PADI6 as a novel marker for oocyte and embryo quality as well as ovarian reserve in women receiving assisted reproductive technologies [96,97].…”
Section: What Are the Functions Of Padi6?mentioning
confidence: 99%
“…Recently, several studies have used RNA-seq to measure the global transcriptomics of oocytes or follicles (Zhang et al, 2020;Jia et al, 2019;Huang et al, 2018;Wang et al, 2017;Liu et al, 2022). Pereira et al, 2020 reported that vitrification and autotransplantation can affect the transcriptomic expression of mouse ovarian tissue.…”
Section: Groupmentioning
confidence: 99%
“…Some genes, such as GDF-9, BMP-4/7/15, KITL, LIF, and FGF-2, are related to primordial follicle growth (Celik et al, 2020). Liu et al (2022) and Sang et al (2021) demonstrated that genes, including Lhx8, Nobox, Sohlh1, Tbpl2, Stk31, and Padi6, might be biomarkers for predicting ovarian reserve. The present study showed that vitrification/warming procedures do not change the aforementioned genes and so these procedures may be a relatively effective method for protecting the ovarian reserve and egg quality.…”
Section: Figurementioning
confidence: 99%
“…In Sertoli cells, the specific expression of PADI2 is involved in testis development by mediating the regulation of target genes by SOX9 regulation ( 12 ). PADI6 is associated with the ovarian reserve (OR) in the primordial follicle pool ( 31 ). During early embryonic development, PADI1 transactivates the early embryonic genome by catalyzing histone tail citrullination.…”
Section: The Padi Family and Reproductive Development-related Diseasesmentioning
confidence: 99%
“…PADI4 can induce arteriosclerosis by mediating the formation of NETs or promote tumor growth and metastasis by altering the tumor microenvironment. Furthermore, PADI6 is associated with the ovarian reserve (OR), oocyte maturation and early embryonic development (27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%